FREEZING CHARACTERISTICS OF TROPICAL FISHES II.TILAPIA (Tilapia mosambica) - SHENOY, A VASANTHA; JAMES, M ARUL (Fishery Technology, 2025)
Tilapia from fresh water and brackish water-sources behaved differently during iced and frozen storage. The former showed an ice storage shelf life of about 13 days while the latter showed signs of spoilage beyond 10 days. In their respective freezing characteristics, the samples from the two sources exhibited far more significant variations. The fresh water type iced for 13 days preserved well for over 24 weeks when frozen and kept at a temperature of -18Â° C, while the brackish water variety held in ice for lO days and subsequently frozen gave a shelf life of only 8 weeks under similar conditions.